Virtues of the Mothers of the Believers From the Manuscript Manhal al-Yanabi‘ in Sharh al-Masabih by al-Sukhumi (d. 774 AH) (with Khadijah, Aisha, and Safiyya, may Allah be pleased with them, as Exemplars) "A Critical Hadith Study (Islamic Sciences Journal, 2026)
This research examines the virtues of the Mothers of the Believers, Khadija, Aisha, and Safiyya (may God be pleased with them), through a study of what is mentioned in the manuscript "Manhal al-Yanabi' fi Sharh al-Masabih" by Imam al-Sakhumi (d. 774 AH). Among those who wrote commentaries on "Masabih al-Sunnah" was Judge Nasir al-Din al-Baydawi (d. 685 AH), who titled his commentary "Tuhfat al-Abrar Sharh Masabih al-Sunnah," as well as other scholars. Due to the importance of this book and my desire to serve the noble Prophetic Hadith, God Almighty facilitated my acquisition of two copies of the manuscript. I then embarked on its investigation and study, relying, after God Almighty, on the major books and sources in various Islamic sciences. This manuscript is considered one of the heritage sources that focused on explaining hadiths of virtues and merits, including those related to the Mothers of the Believers (may God be pleased with them) and the high status they enjoyed as wives of the Prophet (peace and blessings be upon him). It explains their meanings in a precise and scholarly manner. In his commentary, Imam al-Sakhumi mentions four virtues of Lady Khadija and six virtues of the Mothers of the Believers. For Aisha, and one virtue for Safiyya. The research included an introduction, three sections, a conclusion, and a list of sources and references.
Keywords: Virtues; Mothers of the Believers; Manhal al Yanabi‘; Sharḥ al Masābīḥ; al Sukhūmī .